Effectiveness of using g-learning in online lectures for students during the Covid-19 pandemic - Budianto, B; Budi, Rahmad Setia; Warsodirejo, Pandu Prabowo (International Journal for Educational and Vocational Studies, 2022)
This study aims to determine whether G-Suite (Google Learning Application) is effective in student online lectures and can provide a good and efficient academic atmosphere during the Covid-19 pandemic. The research approach uses quantitative with a quasi-experimental type. The data collection technique was carried out through the distribution of online surveys to all students of the Biology Education Study Program, Faculty of Teachers Training and Education, North Sumatra Islamic University (UISU) who learned to use the G-Suite during the Covid-19 pandemic. Based on the calculation results obtained that t-count of 2,901. After being consulted with the t-table at a significance level of 5% and db 68 of 1.990, it turns out that the t-count is greater than the t-table (2.901 > 1.990) so that Ho which reads there is no difference in student outcomes between groups of students taught using the G-Suite and groups of students who were taught without using the G-Suite media have been successfully rejected. Thus, Ha, which reads that there is a significant difference in lecture learning outcomes between groups of students who are taught using G-Suite media and groups of students who are taught without using G-Suite media.